2020
DOI: 10.1128/mra.00700-20
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequences of Seven Uropathogenic Escherichia coli Strains Isolated from Postmenopausal Women with Recurrent Urinary Tract Infection

Abstract: Uropathogenic Escherichia coli (UPEC) is the most common cause of urinary tract infection (UTI). This disease disproportionately affects women and frequently develops into recurrent UTI (rUTI) in postmenopausal women. Here, we report the complete genome sequences of seven UPEC isolates obtained from the urine of postmenopausal women with rUTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…The isolate belongs to the ST2279 lineage (owing to the combination of adk -53, fumC -40, gyrB -47, icd -13, mdh -36, purA -8, and recA -29), which is closely related to the ST131 high-risk clone. It has been reported that the only difference between these two groups is a single nucleotide at position 263 of the purA gene [57] . Few studies have associated ST2279 with isolates from human samples, such as tracheal secretions, urine, and blood [58] , [59] , in accordance with the phylogenetic analysis performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The isolate belongs to the ST2279 lineage (owing to the combination of adk -53, fumC -40, gyrB -47, icd -13, mdh -36, purA -8, and recA -29), which is closely related to the ST131 high-risk clone. It has been reported that the only difference between these two groups is a single nucleotide at position 263 of the purA gene [57] . Few studies have associated ST2279 with isolates from human samples, such as tracheal secretions, urine, and blood [58] , [59] , in accordance with the phylogenetic analysis performed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggest that clonal lineages related to uncomplicated and community-based UTIs may have pathogenic characteristics to adapt to recurrent urinary strains if the appropriate environmental and host factors are present. Interestingly, UTI-1_774U and UTI-3_455U were related to the clinical cUTI strain named EcPF40 in the database, reported by Sharon et al (2020) to be associated with RUTI. Our work supports the proposal to monitor ST1193 as a new clone at the same level of importance as ST131 ( Pitout et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (gDNA) was extracted using Qiagen Blood & Tissue kit and assessed for quality using 260/280nm absorbance ratio, fluorometry, and agarose gel electrophoresis. High quality gDNA libraries were prepared for short-read Illumina and long-read MinION sequencing as described previously (56,60). See detailed methods in Supplemental Materials.…”
Section: Genomic Dna Isolation and Sequencingmentioning
confidence: 99%